Regular Exercise Participation Contributes to Better Proteostasis, Inflammatory Profile, and Vasoactive Profile in Patients With Hypertension. (27th September 2019) - Teixeira, Manuel; Gouveia, Marisol; Duarte, Ana; Ferreira, Miriam; Simões, Maria I; Conceição, Maria; Silva, Gladys; Magalhães, Sandra; Ferreira, Rita; Nunes, Alexandra; Vieira, Sandra I; Ribeiro, Fernando
Abstract: BACKGROUND: Physical exercise is a well-established strategy to control blood pressure. Nonetheless, its effects on protein homeostasis in individuals with hypertension are not clearly defined. AIMS: Evaluate proteostasis, quality of life, and inflammation, oxidative stress, and vasoactive biomarkers in adults with hypertension regarding reported exercise habits. METHODS: Twenty individuals were recruited in a health-care centre, 10 regular exercisers (age: 68.3 ± 4.2 years) and 10 age-matched individuals without regular exercise participation (age: 67.7 ± 5.1 years). Proteostasis and the levels of ubiquitin, heat shock protein 70 (Hsp70), endothelial nitric oxide synthase (eNOS), matrix metalloproteinases 2 (MMP-2), tissue inhibitor of MMP-2 (TIMP-2), connexin 43 (Cx43) and extracellular superoxide dismutase-3 (SOD-3) were assessed in plasma using immunoblotting techniques (western blot or slot blot) and Fourier-transform infrared spectroscopy (FTIR). Quality of life was assessed using the Short Form 36 (SF-36) version 2.0 questionnaire. RESULTS: Significant higher levels of interleukin (IL)-6 ( P = 0.014), eNOS ( P = 0.011), Cx43 ( P = 0.020), TIMP-2 ( P = 0.038), and SOD-3 ( P = 0.001), with a fold increase of 1.5, 1.2, 2.1, 1.3, and 1.2, respectively, were found in the exercise group. The overall quality of life (60.1 ± 4.3 vs. 53.2 ± 5.9, P = 0.009), as well as mental health domain (59.4 ± 7.9 vs. 50.7 ± 7.2, P = 0.024) were significantly higher in the exercise group. Multivariate analysis by FTIR showed that the age-matched group is characterized by peaks related with antiparallel β-sheet, whereas exercise group is characterized by peaks related to random coils, β-sheet, and α-helix. CONCLUSIONS: Individuals with regular exercise participation showed better proteostasis, quality of life, inflammatory profile, antioxidant defenses, and eNOS levels.